Predictors of 6-Month Mortality in Hospitalized COVID-19 Patients, : A Single-Institution Study - Kaur, Jasskiran (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.